The current state and trends of international trade in goods on the example of the Kharkiv region - Posokhov, Igor Mikhailovich; Khodyrieva, O. O.; Marchuk, L. S. (Premier Publishing s.r.o., Austria, 2018)
The development of international trade at the national and regional levels increases the country's foreign trade potential, improves its image, promotes the development of the domestic commodity market. International trade in goods is important for the country's balance of payments and for the movement of capital. The development of international trade in goods of the region testifies to its economic potential.
Keywords: international trade; Kharkiv region; development of the economy